Ten years after 9/11 : rethinking the Jihadist threat - Acharya, Arabinda (London ; New York : Routledge, 2013)
"Ten years after the 9/11 attacks, this book reassesses the effectiveness of the "War on Terror", considers how al-Qaeda and other jihadist movements are faring, explores the impact of wider developments in the Islamic world such as the Arab Spring, and discusses whether all this suggests that a new approach to containing international, especially jihadist, terrorism is needed"--Provided by publisher.
9/11 and globalization of violence -- Construction of the adversary -- Strategy of the global jihadist movement -- Tactics of the global jihadist movement -- Fighting the jihadist threat -- Ten years after : bringing the conflict to an end -- Conclusion : stealing jihadists' playbook, exploiting the fissures within the jihadist movement.
Includes bibliographical references (p. [127]-186) and index.
Keywords: Qaida (Organization); Terrorism -- Prevention; Terrorism -- Religious aspects -- Islam; Jihad; War on Terrorism, 2001-2009.